2019
DOI: 10.1109/tmi.2018.2863562
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis for Retinopathy of Prematurity by Deep Neural Networks

Abstract: Retinopathy of Prematurity (ROP) is a retinal vasproliferative disorder disease principally observed in infants born prematurely with low birth weight. ROP is an important cause of childhood blindness. Although automatic or semiautomatic diagnosis of ROP has been conducted, most previous studies have focused on "plus" disease, which is indicated by abnormalities of retinal vasculature. Few studies have reported methods for identifying the "stage" of ROP disease. Deep neural networks have achieved impressive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“… 29 , 30 For example, a DL system called DeepROP achieved a sensitivity of 96.62% (95% confidence interval, 92.29%–98.89%) and a specificity of 99.32% (95% confidence interval, 96.29%–9.98%) for the detection of ROP (vs no ROP). 31 , 32 Zhao et al 30 reported the development of a DL system that can automatically draw the border of zone 1 on a fundus image as a diagnostic aid. Mulay et al 29 were the first to report the identification of a peripheral ROP ridge (stage) directly in a fundus image.…”
Section: The Development Of Ai Systems For Rop Diagnosismentioning
confidence: 99%
“… 29 , 30 For example, a DL system called DeepROP achieved a sensitivity of 96.62% (95% confidence interval, 92.29%–98.89%) and a specificity of 99.32% (95% confidence interval, 96.29%–9.98%) for the detection of ROP (vs no ROP). 31 , 32 Zhao et al 30 reported the development of a DL system that can automatically draw the border of zone 1 on a fundus image as a diagnostic aid. Mulay et al 29 were the first to report the identification of a peripheral ROP ridge (stage) directly in a fundus image.…”
Section: The Development Of Ai Systems For Rop Diagnosismentioning
confidence: 99%
“…Since 2012, when AlexNet 12 won the 2012 ILSVRC competition, 13 numerous important breakthroughs in computer vision have been achieved using DCNNs. [14][15][16] To automatically predict treatment planning for patients who need radiotherapy, and benefit from the development of DCNNs, previous studies used DCNNs to build a model to predict dose distribution. [2][3][4] The similarity of these studies is that they constructed dose prediction models based on the treatment planning of patients treated with IMRT.…”
Section: Dose Predictionmentioning
confidence: 99%
“…Na osnovu prethodnih radova na ovu temu [4,5,6], izabran je podskup metoda mašinskog učenja koje su dale najbolje rezultate. Odabrane su konvolutivne neuronske mreže za koje se smatra da su trenutno najperspektivnije za problem detekcije.…”
Section: Napomenaunclassified